RSVDの計算
をテンプレートにして作成
[
トップ
] [
新規
|
一覧
|
単語検索
|
最終更新
|
ヘルプ
]
開始行:
\(p_{uk}\)の更新式
$$
\begin{array}{l}
p_{uk} - \alpha \frac{\partial}{\partial p_{uk}} \left( \...
= p_{uk} - \alpha \frac{\partial}{\partial p_{uk}} \left\...
= p_{uk} - \alpha \sum_{i \in T} \frac{\partial}{\partia...
= p_{uk} - \alpha \sum_{i \in T} \left\{ { e_{ui} \frac...
= p_{uk} - \alpha \sum_{i \in T} \left\{ e_{ui} \frac{\p...
= p_{uk} - \alpha \sum_{i \in T} \left\{ e_{ui} q_{k i} ...
= p_{uk} - \alpha \left( \sum_{i \in T} e_{ui} q_{k i} ...
\end{array}
$$
$$
p_{uk} - \alpha \frac{\partial}{\partial p_{uk}} \left( \...
$$
$$
= p_{uk} - \alpha \frac{\partial}{\partial p_{uk}} \left\...
$$
$$
= p_{uk} - \alpha \sum_{i \in T} \frac{\partial}{\partia...
$$
$$
= p_{uk} - \alpha \sum_{i \in T} \left\{ { e_{ui} \frac...
$$
$$
= p_{uk} - \alpha \sum_{i \in T} \left\{ e_{ui} \frac{\p...
$$
$$
= p_{uk} - \alpha \sum_{i \in T} \left\{ e_{ui} q_{k i} ...
$$
$$
= p_{uk} - \alpha \left( \sum_{i \in T} e_{ui} q_{k i} ...
$$
終了行:
\(p_{uk}\)の更新式
$$
\begin{array}{l}
p_{uk} - \alpha \frac{\partial}{\partial p_{uk}} \left( \...
= p_{uk} - \alpha \frac{\partial}{\partial p_{uk}} \left\...
= p_{uk} - \alpha \sum_{i \in T} \frac{\partial}{\partia...
= p_{uk} - \alpha \sum_{i \in T} \left\{ { e_{ui} \frac...
= p_{uk} - \alpha \sum_{i \in T} \left\{ e_{ui} \frac{\p...
= p_{uk} - \alpha \sum_{i \in T} \left\{ e_{ui} q_{k i} ...
= p_{uk} - \alpha \left( \sum_{i \in T} e_{ui} q_{k i} ...
\end{array}
$$
$$
p_{uk} - \alpha \frac{\partial}{\partial p_{uk}} \left( \...
$$
$$
= p_{uk} - \alpha \frac{\partial}{\partial p_{uk}} \left\...
$$
$$
= p_{uk} - \alpha \sum_{i \in T} \frac{\partial}{\partia...
$$
$$
= p_{uk} - \alpha \sum_{i \in T} \left\{ { e_{ui} \frac...
$$
$$
= p_{uk} - \alpha \sum_{i \in T} \left\{ e_{ui} \frac{\p...
$$
$$
= p_{uk} - \alpha \sum_{i \in T} \left\{ e_{ui} q_{k i} ...
$$
$$
= p_{uk} - \alpha \left( \sum_{i \in T} e_{ui} q_{k i} ...
$$
ページ名:
SmartDoc